Aeronomics and Law - Abeyratne, Ruwantissa. author. aut Link
XII, 196 p.
Keywords: This book embarks on a contemporary analysis of the interaction of economics and law relating to air transport, delving into the major issues that plague the industry. It shows how some of the thorny and frustrating issues could be approached sensibly. Among the issues discussed are the anomaly of exponential growth of air transport which makes airline profitability continue to be poor; the legislative impediments in most countries that preclude direct foreign investment in the industry; the confounding and muddled mess behind the economics of aircraft engine emissions; and the inexplicable reality that, although civil aviation is primarily meant to meet the needs of the people of the world, State regulators have upended the equation and given priority to national interests over the interests of the passenger. This book will be of interest to economists and lawyers alike who deal with air transport issues, and also to academics and students in the area of transportation as well as regulators and airlines. Dr. Ruwantissa Abeyratne has worked in the field of aviation law and management for thirty years and is currently Senior Legal Officer at the International Civil Aviation Organization. He has published 20 books and numerous journal articles on air law and economics.